Pepper in a time of crisis: price booms, government subsidies and smallholder response during and after the Asian economic crisis - Wadley, R.L.; Sissman, K. (University of Copenhagen, 2003)
Beginning in 1997, international prices for black pepper (Piper nigrum L.) boomed for about three years, coinciding with the Asian economic crisis. Smallholders throughout Southeast Asia responded to the price rises by investing more labor into existing pepper gardens as well as planting new gardens. While this is part of an old pattern with such boom-and-bust cash crops, the unique historical circumstance surrounding the most recent boom was the Asian crisis. Here we compare the response of Iban pepper smallholders to this situation on either side of the international border separating Sarawak, Malaysia and West Kalimantan, Indonesia. On both sides, Iban benefited from the higher prices, but many households without productive vines at the onset of high prices were too late as their new gardens had hardly matured before prices fell in 2000. In the study communities, the Iban Kalimantan significantly reduced their labor migration to focus on pepper during the period of high prices, whereas the Sarawak Iban relied on rather specific off-farm income sources in the tourism, off-shore oil and gas industries, and did not significantly alter their pepper cultivation strategies. The mutual buffering capacity of hill rice cultivation and pepper farming described in an earlier study in Sarawak was not evident in the study communities.